2022
DOI: 10.1002/jcp.30706
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral myelin protein 22 in chronic exercise‐induced interactions of muscle and bone in mice

Abstract: Exercise is important for the prevention and treatment of sarcopenia and osteoporosis.Although the interactions between skeletal muscles and bone have recently been reported, the myokines linking muscle to bone during exercise remain unknown. We previously revealed that chronic exercise using treadmill running blunts ovariectomyinduced osteopenia in mice. We herein performed an RNA sequence analysis of the gastrocnemius and soleus muscles of male mice with or without chronic exercise to |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…We previously revealed that irisin, follistatin, dickkopf 2, and peripheral myelin protein 22 produced by the skeletal muscles are related to the bone changes induced by changes in mechanical stress and gravity levels or exercise 913 . On the other hand, a diabetic state, vitamin D deficiency, and glucocorticoid excess suppress the expressions of several myokines, including irisin, IGF-1, and FGF2, in the skeletal muscles of mice 14 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously revealed that irisin, follistatin, dickkopf 2, and peripheral myelin protein 22 produced by the skeletal muscles are related to the bone changes induced by changes in mechanical stress and gravity levels or exercise 913 . On the other hand, a diabetic state, vitamin D deficiency, and glucocorticoid excess suppress the expressions of several myokines, including irisin, IGF-1, and FGF2, in the skeletal muscles of mice 14 15 .…”
Section: Introductionmentioning
confidence: 99%